2021
DOI: 10.1039/d1cs00633a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic lipid aptamers: non-polymeric chemical path to early life

Abstract: Mixed lipid assemblies form dynamic aptamers that possess protein-like stereospecific recognition. This capacity can mediate assembly self-reproduction, supporting an early role for lipids in life's origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…An odor could directly bind (1) to the odor receptor through the mucus, or the odor could bind and change the fluidity or structure of the lipid membrane (2) to enhance odorant access to the odor receptors, depending on the partitioning of the odorant into the lipid bilayer. The accumulation of odorants in the lipid bilayer may lead to structural changes (3), for instance raft-like structures that could regulate one or more of the membrane-bound proteins illustrated in Figure 7 [ 27 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An odor could directly bind (1) to the odor receptor through the mucus, or the odor could bind and change the fluidity or structure of the lipid membrane (2) to enhance odorant access to the odor receptors, depending on the partitioning of the odorant into the lipid bilayer. The accumulation of odorants in the lipid bilayer may lead to structural changes (3), for instance raft-like structures that could regulate one or more of the membrane-bound proteins illustrated in Figure 7 [ 27 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of several GPCRs has been found to be regulated by lipid composition, for instance the cholesterol content of the lipid membrane [ 30 , 31 , 32 ]. Combinations of lipids have been proposed to play more than just a supporting role for proteins in biological systems [ 33 , 34 , 35 ]. For instance, in a model system it was shown that aggregates of lipid-like molecules can demonstrate molecular recognition as a kind of supramolecular aptamer [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is even more so since all these structures are highly dynamic [ 27 ]. They easily form and disintegrate under cyclic conditions such as wet–dry cycling or periodic phase transitions [ 26 ], and they may have even undergone steps of self-organization on their own [ 32 , 33 ]. In addition, and this may be the most important aspect, they themselves can be subject to a second stage of selection.…”
Section: The Potential Nature Of a “Selector”mentioning
confidence: 99%
“…In this case, mutual-catalysis describes the predicted capacity of lipids to modify the rates of entry and exit of other lipid types to and from a micellar assembly, though synthetic reactions have also been explored in the context of the GARD model [11]. The model predicts that the micellar lipids act on accreting lipids in a coordinated fashion, as observed in published reports [12,14]. These catalytic exertions may lead to compositional homeostasis, a unique state in which the assembly's composition remains unchanged throughout growth-and-split cycles [11,15].…”
Section: Introductionmentioning
confidence: 95%